Visible and near-infrared luminescent Eu3+ or Er3+ doped laponite-derived xerogels and thick films: Structural and spectroscopic properties - Tronto, Jairo; Lima Ribeiro, Sidney Jose [UNESP]; Valim, Joao Barros; Goncalves, Rogeria Rocha (Elsevier B.V. Sa, 2009)
Laponite-derived materials represent promising materials for optical applications. In this work, Eu3+- or Er3+-doped laponite xerogels and films were prepared from colloidal dispersion. Homogeneous, crack-free and transparent single layers were deposited on soda-lime substrates with a thickness of 10 mu m. Structural and spectroscopic properties were analyzed by thermal analyses, X-ray diffractometry, transmission electron microscopy, infrared spectroscopy, and luminescence spectroscopy. The addition of a rare earth ion to the laponite does not promote any changes in thermal stability or phase transition. Laponite clay was identified after annealing up to 500 degrees C, with a decrease in basal spacing when the annealing temperature is changed from 100 degrees C to 500 degrees C. Enstatite polymorphs and amorphous silicate phases were observed after heat treatment at 700 degrees C and 900 degrees C. Stationary and time-dependent luminescence spectra in the visible region for Eu3+, and D-5(0) lifetime are discussed in terms of thermal treatment and structural evolution. In the layered host, the Eu3+ ions are distributed in many different local environments. However, Eu3+ ions were found to occupy at least two symmetry sites, and the ions are preferentially incorporated into the crystalline enstatite for the materials annealed at 700 degrees C and 900 degrees C. A D-5(0) lifetime of 1.3 ms and 3.1 ms was obtained for Eu3+ ions in an amorphous silicate and crystalline MgSiO3 local environment, respectively. Strong Er3+ emission at the 1550 nm region was observed for the materials annealed at 900 degrees C, with a bandwidth of 44 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Clays; Laponite; Rare earth; Europium; Erbium; Xerogels; Films and silicate